Expression of Prophetic Variables of Analytical Importance and their Potential Role in Breast Cancer Patient Underwent Surgical Procedure - Amina Shahid, Anoosh Qayyum, Khalida Anwar, Nusrat Tariq, Sultan Ahmad, Naveed Shuja, Sara Zahid, Sulayman Waquar, Arif Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Study the role of prophetic variables and their role in breast cancer patients especially those underwent surgical procedures. Study Design: Cross-sectional study Place and Duration: Institute of Molecular Biology and Biotechnology (IMBB), The University of Lahore. Martials and Methods: Twenty diagnosed patients of breast cancer facing surgical procedure were selected from the surgical department, Jinnah hospital, Lahore and twenty normal females were included in the study. Complete blood count (CBC) of the selected individuals was performed. Other biochemical markers Malondialdehyde (MDA), 8-hydroxy-2-deoxyguanosine (8-OHdG), 4-Hydroxynonenol (4-HNE), Isoprostanes F2α (IsoP- F2α), Interleukin-6 (IL-6), Matrix metalloproteinases-9 (MMP-9), Tumor Necrosis factor-alpha (TNF-α), Prostaglindin-E2 (PGE-2) were measured by commercially available kits. Results: The mean weight, BMI, WBCs, platelet count, lymphocyte and neutrophil value were higher in patients compared to the controls with statistically significant differences (p< 0.05). However, the mean MDA, 8-OHdG, 4-HNE, Iso-P2α, IL-6, MMP-9, TNF-α and PGE-2 value significantly higher than the control subjects (p < 0.05). Conclusion: Findings of the study demonstrated the significant role of the said prophetic variables that were having their medicinal importance in the invagination of breast cancer among the patients undergone surgical interventions. It shows the significant increases in the levels of discussed markers that show increased oxidative stress leading to cell damage that can be observed within the studied group. Therefore, early investigation of the said variables and ruling out the true causes could help in addressing the oncological complications that one undergoes after being through the surgical interventions and in providing the best possible treatments Keywords: Epidermal growth factor receptor, metastatic invasion, breast cancer surgery, matrix metalloproteinase, DNA adduct